Navigating Travel Challenges for Individuals with Stomas: A Systematic Review - Lee, Pei-Tsan (South East Asia Nursing Research, 2023)
Travel can present unique challenges for individuals with stomas, including concerns about accessibility, hygiene, and security procedures. This systematic review synthesizes current research on the difficulties faced by stoma patients during travel and offers recommendations for healthcare providers and patients. The review includes studies on the psychological impact of travel-related anxiety, practical issues such as managing stoma supplies, and strategies for ensuring comfort and safety while traveling. The findings suggest that with appropriate planning and support, stoma patients can travel confidently and comfortably.